Pericytic porters: helping leptin step in. (December 2021) - Torres, Daniel J.; Pitts, Matthew W.
Abstract : A new mechanism of leptin extravasation from the bloodstream into the brain may have been discovered. According to recent findings by Butiaeva et al ., pericytes within the blood–brain barrier (BBB) express the leptin receptor and, upon activation, facilitate the movement of the appetite-suppressing hormone into deeper regions of the hypothalamus.